Revista senderos pedagogicos (Facultad de Educación y Ciencias Sociales del Tecnológico de Antioquia, 2010)
Devoted to research and scholarship in education.
Keywords: Education : Periodicals; Education and state : Colombia : Periodicals; Social sciences : Periodicals